THE EFFECT OF HERDING BEHAVIOR AND OVERCONFIDENCE ON INTEREST IN INVESTING IN SHARIA STOCKS: THE ROLE OF INCOME AS MODERATING - Hafidhah; Khairul Amri; Ismail (Universitas Sultanah Nahrasiyah, 2025)
This study aims to analyze the effect of herding behavior and overconfidence on interest in investing in Sharia stocks, moderated by income (study at the Sharia Investment Gallery of the Faculty of Islamic Economics and Business, UIN Ar-Raniry Banda Aceh). This is a quantitative study, with a sample size of 100 respondents. The sampling technique used was Simple Random Sampling through data collection using an online questionnaire via Google Form. The data analysis techniques used in this study are Structural Equation Modelling (SEM) and Moderated Regression Analysis (MRA), employing Smart PLS 4.0 and SPSS for data processing. The results of the study indicate that herding behavior, overconfidence, and income have a positive and significant effect on interest in investing in Sharia stocks. Income can moderate the effect of herding behavior on interest investing in Sharia stocks, but it cannot moderate the effect of overconfidence on interest in investing in Sharia stocks